Major elements chemical composition of internal layers of VA 13/2 (station 237 KD) ferromanganese crusts - Ulrich von Stackelberg; Helmar Kunzendorf; Vesna Marchig; R Gwozdz (PANGAEA, 2022)
On the basis of the macroscopically visible layers, chemical analyses were carried out on various ferromanganese crust samples from VA 13/2 (sample 237 KD) for Mn, Fe, Ni, Cu, Co, Pb, Zn, Al, Ca and Ba by atomic absorption spectroscopy (AAS) at the exception of SiO2 by Gravimetric method.